Toxina botulínica y su importancia en el campo de la rehabilitación - Moyano V., Álvaro; Cubillos O., Fernando; Maldonado A., Paula; San Martín, Eduardo (Revista Hospital Clínico Universidad de Chile, 2010)
Botulinum toxin, the most potent biological toxin, has become a powerful therapeutic tool for a growing number of clinical applications. It produces temporary denervation manifested by paralysis of muscles treated. Also inhibits the release of neurotransmitters involved in nociceptive stimuli. With the presence of Botulinum toxin inside the rehabilitation field has enabled major advances in the management of patients with neurological diseases and musculoskeletal pain.